Hybrid Nanoparticles as an Efficient Porphyrin Delivery System for Cancer Cells to Enhance Photodynamic Therapy - Silva, Letícia B.; Castro, Kelly A. D. F.; Botteon, Caroline E. A.; Oliveira, Cristiano L. P.; da Silva, Roberto S.; Marcato, Priscyla D. (Frontiers in Bioengineering and Biotechnology, 2021)
Photodynamic therapy (PDT) is a potential non-invasive approach for application in oncological diseases, based on the activation of a photosensitizer (PS) by light at a specific wavelength in the presence of molecular oxygen to produce reactive oxygen species (ROS) that trigger the death tumor cells. In this context, porphyrins are interesting PS because they are robust, have high chemical, photo, thermal, and oxidative stability, and can generate singlet oxygen (1O2). However, porphyrins exhibit low solubility and a strong tendency to aggregate in a biological environment which limits their clinical application. To overcome these challenges, we developed hybrid nanostructures to immobilize 5,10,15,20-tetrakis[(4-carboxyphenyl) thio-2,3,5,6-tetrafluorophenyl] (P), a new third-generation PS. The biological effect of this system was evaluated against bladder cancer cells with or without light exposition. The nanostructure composed of lipid carriers coated by porphyrin-chitosan (P-HNP), presented a size of ca. 130 nm and low polydispersity (ca. 0.25). The presence of the porphyrin-chitosan (P-chitosan) on lipid nanoparticle surfaces increased the nanoparticle size, changed the zeta potential to positive, decreased the recrystallization index, and increased the thermal stability of nanoparticles. Furthermore, P-chitosan incorporation on nanoparticles increased the stability and enhanced the self-organization of the system and the formation of spherical structures, as observed by SAXS analysis. Furthermore, the immobilization process maintained the P photoactivity and improve the photophysical properties of PS, minimizing its aggregation in cell culture medium. In the photoinduction assays the P-HNP displayed high phototoxicity with IC50 3.2-folds lower than free porphyrin. This higher cytotoxic effect can be correlated to the high cellular uptake of porphyrin immobilized, as observed by confocal images. Moreover, the coated nanoparticles showed mucoadhesive properties interesting to its application in vivo. Therefore, the physical and chemical properties of nanoparticles may be relevant to improve the porphyrin photodynamic activity in bladder cancer cells.